Effectiveness and safety of endoscopic ultrasound-guided radiofrequency ablation for pancreatic metastases of renal cell carcinoma. - Stouvenot, Morgane; Koch, Stephane; Frontzcak, Alexandre; D'Engremont, Christelle; Boinette, Aurélien; Doussot, Alexandre; Maurina, Tristan; Vuitton, Lucine (Endoscopy International Open, 2025)
Pancreatic metastases from renal cell carcinoma (RCC) are usually managed surgically but with significant morbidity. As an alternative, endoscopic ultrasound-guided radiofrequency ablation (EUS-RFA) has shown promising results in treatment of pancreatic neuroendocrine tumors. The aim of our study was to assess technical success, effectiveness, and safety of EUS-RFA in patients with pancreatic metastases of RCC.This retrospective, observational study included consecutive patients referred for EUS-RFA of pancreatic RCC metastases. EUS-RFA was performed through 18G or 19G dedicated RFA needles. Effectiveness of EUS-RFA treatment was defined by necrosis with no contrast enhancement or lesion disappearance, determined by contrast-enhanced computed tomography (CT) scan, at 2 to 5 months post procedure, 1 year, and at the end of follow-up. Safety was assessed per and post procedure.Between January 2015 and January 2021, eight patients with 11 lesions were treated and median time from RCC diagnosis to pancreatic metastases RFA was 8.5 years (1–15). Mean lesion size was 13.9 mm (± 3.9). Technical success assessed by immediate post procedure contrast-enhanced CT or Doppler was 100%. At the first CT scan follow-up, complete response was 45.4% and partial response was 27.3%. At 1 year, complete response was 45.4% and partial response was 27.3%. Three patients had multiple EUS-RFAs. Adverse events occurred in 3 patients (mild acute pancreatitis, abdominal pain, and pancreatic fistula with retro-gastric pseudocyst).Our study demonstrated the feasibility and safety of EUS-RFA for patients with pancreatic metastases of RCC.
Keywords: Endoscopic ultrasonography; Pancreas; Intervention EUS